Pengaruh profitabilitas, struktur aktiva, dan likuiditas terhadap struktur modal pada perusahaan makanan minuman yang terdaftar di Bursa Efek Indonesia pada tahun 2014-2017 - Nabayu, Yona Putri; Marbun, Novelia; Ginting , Hannitra Fitria; Sebayang , Novi Adriyani; Sipahutar, Tetty Tiurma Uli (Jurnal Paradigma Ekonomika, 2020)
The purpose of conducting this research is to examine the effect of profitability, asset structure, liquidity, on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange in 2014-2017. This study used a sample of 36 food and beverage companies listed on the Indonesia Stock Exchange in 2014-2017. The approach method used in this research is quantitative, the type of research used is descriptive quantitative, the nature of this research is causal and the type of secondary data. Multiple linear regression is used in the data analysis method. Judging from the results of this study that profitability partially does not affect capital structure while asset structure partially has a negative and significant effect on capital structure and liquidity has a positive and significant effect on capital structure. Simultaneously, profitability, asset structure, liquidity have a positive and significant impact on capital structure. The results of the coefficient and determination test obtained an adjusted R Square value of 0.252 or 25.2%, this means that the dependent variable, namely the capital structure can be explained by variations of the four independent variables, namely profitability, asset structure and liquidity by 25.2%, while the remaining 74.8% is explained by other variables not included in this study.